(untitled) (SAARC Journal of Agriculture, 2019)
Farmers’ choice of drought adaptation measures depends on several determinants that include their socioeconomic, demographic, and agricultural characteristics. This study aimed to investigate the presence of dependency or association between the adaptation strategies implemented by farmers’ own initiative and their determinants in the Barind Tract of Bangladesh. The study was mainly based on primary data collected through a household level survey using a structured questionnaire covering 400 farming households from an extended area comprising 10 Unions from 03 Districts, viz. Rajshahi, Chapai Nawabganj, and Naogaon in northwest Bangladesh. The chi-square test and Cramer’s V test has been applied to measure the association between variables and the strength of the association respectively. The study found that the nature of adaptation strategies implemented by farmers is mainly related to crop production and income generation. Their capability noticeably lacks to facilitate artificial irrigation that made them dependent on government’s initiatives. The association between the implemented adaptation measures and selected variables suggests that the farm size, irrigation accessibility, monthly household income, land ownership status, literacy level, and poverty status played significant role in the implementation of adaptation measures. Finally, limitations of currently practiced adaptation strategies and future way forwardhave been discussed for better drought risk management. SAARC J. Agri., 17(1): 161-174 (2019)